IMPLIKASI BERLAKUNYA PERATURAN PEMERINTAH NOMOR 46 TAHUN 2017 TENTANG INSTRUMEN EKONOMI LINGKUNGAN HIDUP TERHADAP KONSERVASI TANAH DAN AIR (Implication of Goverment Regulation Number 46 of 2017 Concerning Environmental Economical Aspect Towards Water and Soil Conservation) - Albertus Sentot Sudarwanto (Jurnal Penelitian Pengelolaan Daerah Aliran Sungai (Journal of Watershed Management Research), 2020)
ABSTRACTIf the upstream community carries out the Soil and Water Conservation (SWC), whereas thedownstream community participates in the benefits, therefore the upstream community needs to be rewarded with Payment Environmental Services (PES). This writing aims to analyze the logical consequences of the regulation of environmental economic instruments toward the SWC, especially related to environmental services. The research method is a normative juridical approach, using secondary data consisting of primary and secondary legal materials using qualitative analysis techniques. The results of the study show that the PES has been regulated in Government Regulation Number 46 of 2017 on Environmental Economic Instruments but there is no detailed regulation related to the calculation of SWC environmental services performed by downstream communities toward upstream communities. The Watershed Management Coordination Forum together with the government formed an Ad Hoc team whose task was to manage environmental service funds. Downstream communities pay for environmental services to the upstream communities as service providers through the environmental service management agencies. Therefore, the Ministry of Environment and Forestry of the Republic of Indonesia needs to immediately compile technical regulations on the mechanism and calculation of SWC from communities and governments in the downstream region to the government and communities in the upstream region.Keywords: Implication; instruments of living environmental economic; soil and water Conservation ABSTRAKApabila masyarakat wilayah hulu melakukan Konservasi Tanah dan Air (KTA), masyarakat bagian hilir ikut merasakan manfaatnya, oleh sebab itu masyarakat hulu perlu diberi Imbal Jasa Lingkungan (IJL). Penulisan ini bertujuan menganalisis konsekuensi logis pengaturan tentang instrumen ekonomi lingkungan hidup terhadap KTA khususnya terkait dengan jasa lingkungan. Metode penelitian dengan pendekatan yuridis normatif, menggunakan data sekunder yang terdiri dari bahan hukum primer dan bahan hukum sekunder dengan Teknik analisis secara kualitatif. Hasil kajian menunjukkan IJL telah diatur dalam Peraturan Pemerintah Nomor 46 Tahun 2017 Tentang Instrumen Ekonomi Lingkungan Hidup tetapi belum ada pengaturan secara rinci terkait penghitungan jasa lingkungan KTA yang dilakukan oleh masyarakat hilir kepada masyarakat hulu. Forum Koordinasi Pengelolaan DAS Bersama pemerintah membentuk tim Ad Hoc yang memiliki tugas mengelola dana jasa lingkungan. masyarakat hilir membayar jasa lingkungan kepada masyarakat hulu sebagai penyedia jasa melalui lembaga pengelola jasa lingkungan. Oleh karena itu, Kementerian Lingkungan Hidup dan Kehutanan RI perlu segera menyusun peraturan teknis tentang mekanisme dan penghitungan IJL KTA dari masyarakat dan pemerintah di wilayah hilir kepada pemerintah dan masyarakat di wilayah hulu.Kata kunci: Implikasi; Instrumen Ekonomi Lingkungan Hidup; KTA; DAS